2018
DOI: 10.1111/jcmm.13824
|View full text |Cite
|
Sign up to set email alerts
|

Secretion of heat shock ‐60, ‐70 kD protein, IL‐1β and TNFα levels in serum of a term normal pregnancy and patients with pre‐eclampsia development

Abstract: The extracellular heat shock proteins (eHsp) family act as molecular chaperones regulating folding, transporting protein and are associated with immune modulation in different physiological and pathological processes. They have been localized in different gestational tissues and their concentration in amniotic fluid and serum has been determined. In the present study, we proposed to determine the concentration of eHsp‐60, ‐70, IL‐1β and TNFα in the serum of pregnant patients with 34 weeks of gestation with and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 15 publications
3
19
2
Order By: Relevance
“…It is a common and severe complication encountered during pregnancy (22,23). Patients with pre-eclampsia often suffer from increased uric acid levels and serum transaminase concentrations (24). Currently, the only effective treatment for pre-eclampsia is delivery or interruption of pregnancy (25).…”
Section: Discussionmentioning
confidence: 99%
“…It is a common and severe complication encountered during pregnancy (22,23). Patients with pre-eclampsia often suffer from increased uric acid levels and serum transaminase concentrations (24). Currently, the only effective treatment for pre-eclampsia is delivery or interruption of pregnancy (25).…”
Section: Discussionmentioning
confidence: 99%
“…Levels of TNFa, interleukins, CRP, and HSP circulate at elevated concentrations in maternal serum of women who develop preeclampsia. [69][70][71][72][73][74][75][76] High levels of CRP correlate with increased titers of anti-Cp IgG antibodies in women with preeclampsia requiring delivery before term. 77 We do not consider that the early gestational age at delivery seen in cases with preeclampsia influenced the elevated levels of anti-Cp IgG antibodies, CRP, or increased sFlt-1/PlGF ratio when compared to healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, elevated HSP70 seems to suppress NO levels mediating this abnormality ( Lai et al, 2020 ). Álvarez-Cabrera et al (2018) found that serum levels of HSP60 were also elevated in preeclamptic subjects. The exceptionally high levels of HSP70 in treatment-resistant pre-term delivery cases suggest that HSP70 may be a valuable marker for assessing the curative effects of pre-term delivery treatment ( Fukushima et al, 2005 ).…”
Section: Heat Shock Proteins and Adverse Pregnancy Outcomementioning
confidence: 95%
“…Conversely, the increased circulating levels of HSP70 were found to be associated with several pregnancy complications including pre-eclampsia and syndrome of hemolysis, elevated liver enzymes and low platelet count (HELLP syndrome) ( Molvarec et al, 2006 ; Molvarec et al, 2007 ; Madách et al, 2008 ; Molvarec et al, 2011 ; Peraçoli et al, 2013 ; Álvarez-Cabrera et al, 2018 ). In preeclamptic women, the elevated serum HSP70 level may be a marker of systemic inflammation, oxidative stress and hepatocellular injury ( Molvarec et al, 2009 ; Álvarez-Cabrera et al, 2018 ). It is believed that the HSP70 mediated generation of proinflammatory immune responses may be one of the reasons behind maternal immune directed rejection of the fetus ( Molvarec et al, 2010 ).…”
Section: Heat Shock Proteins In Decidualizationmentioning
confidence: 99%